2015
DOI: 10.1111/bph.12825
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous administration of thiosulfate, a donor of hydrogen sulfide, attenuates angiotensin II‐induced hypertensive heart disease in rats

Abstract: BACKGROUND AND PURPOSEHypertension is an important mediator of cardiac damage and remodelling. Hydrogen sulfide (H2S) is an endogenously produced gasotransmitter with cardioprotective properties. However, it is not yet in clinical use. We, therefore, investigated the protective effects of sodium thiosulfate (STS), a clinically applicable H2S donor substance, in angiotensin II (Ang II)-induced hypertensive cardiac disease in rats. EXPERIMENTAL APPROACHMale Sprague Dawley rats were infused with Ang II (435 ng kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
69
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 60 publications
7
69
0
Order By: Relevance
“…H 2 S decreased the expression of the P47 NADPH oxidase subunit, which is related to oxidative stress stimulation via the NF-κB pathway. Some studies demonstrated that treatment with exogenous H 2 S suppresses the expression of pro-fibrotic genes fibronectin and galectin-3 mRNA levels, and the expression of fibrotic marker CTGF in AngII-stimulated cardiac fibroblasts [14,41,42]. Our previous studies have shown that NaHS (a H 2 S donor) was potent at inhibiting NOX4 expression and activity under oxidative stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 S decreased the expression of the P47 NADPH oxidase subunit, which is related to oxidative stress stimulation via the NF-κB pathway. Some studies demonstrated that treatment with exogenous H 2 S suppresses the expression of pro-fibrotic genes fibronectin and galectin-3 mRNA levels, and the expression of fibrotic marker CTGF in AngII-stimulated cardiac fibroblasts [14,41,42]. Our previous studies have shown that NaHS (a H 2 S donor) was potent at inhibiting NOX4 expression and activity under oxidative stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Its solution stability combined with its ability to serve as a source of sulfane sulfur makes thiosulfate a potentially ideal ‘Trojan horse’ RSS that, upon activation by a specific sulfurtransferase, can mobilize its terminal sulfur for transfer. The role of thiosulfate in sulfide-based signaling needs to be assessed, particularly in light of recent reports of its therapeutic potential in acute lung injury 76 and hypertensive cardiac disease 77 . The archaeon Metallosphaera cuprina utilizes tetrathionate as an energy source and, interestingly, transfers the thiosulfate group between cysteines in proteins involved in dissimilatory sulfur metabolism 78 .…”
Section: Mitochondrial H2s Oxidation Pathway: a Source Of Rss?mentioning
confidence: 99%
“…Another promising treatment option is the H2S metabolite TS in the form of STS [113,114]. Because of the dynamic conversion between TS and H2S, TS can function as an H2S donor [115].…”
Section: H2s Treatment Modalitiesmentioning
confidence: 99%